Minimally manipulated murine regulatory T cells purified by reversible Fab Multimers are potent suppressors for adoptive T‐cell therapy. Issue 12 (15th September 2017) - Mohr, Fabian; Fischer, Julius Clemens; Nikolaus, Marc; Stemberger, Christian; Dreher, Stefan; Verschoor, Admar; Haas, Tobias; Poeck, Hendrik; Busch, Dirk H.
Abstract: The transfer of regulatory T cells, either freshly isolated, or modified, represents a promising therapeutic approach to dampen misdirected immune responses, like autoimmune diseases, chronic inflammatory syndromes and graft versus host disease. Clinical isolation of highly pure regulatory T cell (Treg) populations is still challenging and labeling reagents can influence their viability and functionality, potentially altering the potency of isolated Treg cell products. Here we show that reversible Fab multimer‐based Treg purification can prevent conventional antibody label‐induced interferences in vitro and in vivo. Remaining isolation reagents negatively interfere with Treg engraftment efficacy in C57BL/6 wild‐type mice due to Fcγ‐receptor‐ as well as IL‐2 receptor‐mediated mechanisms. Using a preclinical model for acute GvHD, we further show that purified 'label‐freed' Tregs are protective at substantially lower cell numbers as compared to conventional nonreversible antibody staining, translating into significantly improved survival of mice treated with minimally manipulated Tregs. These findings have important clinical relevance for future Treg‐based cell therapies. Abstract : We developed a one‐step positive enrichment protocol for highly pure regulatory T cell that allowed subsequent release of the isolation reagent from the cell surface using Fab multimers. This removal of isolation reagents led to better engraftment of Treg cells and to better in vivo protection from experimental acute GvHD.